2011
DOI: 10.1007/s10681-011-0512-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of resistance to nematodes in inbred maize (Zea mays L.) and maize hybrids

Abstract: Nematodes cause substantial grain yield loss in susceptible maize (Zea mays L.) cultivars. This study was conducted to estimate general combining ability (GCA), specific combining ability (SCA) and genetic effects associated with nematode resistance in maize. The 30 F 1 hybrids generated from a 6 9 6 diallel and two local checks were evaluated in 2009 at three sites in Uganda. A split plot design was used with nematode treatments serving as whole plots and the hybrids as subplots but arranged in an 8 9 4 spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…It corroborates other studies for resistance to northern leaf blight in maize, 77,114 gray leaf spot in maize, 77 stem canker in sunflower (Phomopsis helianthi), 11 Fusarium root rot in common bean, 115 cassava brown streak in cassava, 6 root-lesion nematodes (Pratylenchus thornei and P. neglectus) in wheat, 116 and P. zeae and Meloidogyne spp. nematodes density in maize 76 but differ from recent study by Akinwale et al, 92 who found a greater manifestation of SCA in control of the number of emerged Striga plants under Striga infestation in maize Table 5. Recently, Derera et al, 101 found maize weevil resistance to be under the control of both GCA and SCA effects.…”
Section: Combining Ability For Pest Resistancecontrasting
confidence: 67%
See 1 more Smart Citation
“…It corroborates other studies for resistance to northern leaf blight in maize, 77,114 gray leaf spot in maize, 77 stem canker in sunflower (Phomopsis helianthi), 11 Fusarium root rot in common bean, 115 cassava brown streak in cassava, 6 root-lesion nematodes (Pratylenchus thornei and P. neglectus) in wheat, 116 and P. zeae and Meloidogyne spp. nematodes density in maize 76 but differ from recent study by Akinwale et al, 92 who found a greater manifestation of SCA in control of the number of emerged Striga plants under Striga infestation in maize Table 5. Recently, Derera et al, 101 found maize weevil resistance to be under the control of both GCA and SCA effects.…”
Section: Combining Ability For Pest Resistancecontrasting
confidence: 67%
“…These four methods have been widely used to study the patterns of inheritance of different traits in many crops. 27,28,76,77 These diallel methods of Griffing 71 are generally used for one year or one location trials however, multienvironment trials are suggested to produce more reliable genetic information on material tested. 78 Moreover, it has been illustrated that the early information on the genetic behaviour of these traits can be obtained by diallel cross method.…”
Section: Diallel Designmentioning
confidence: 99%
“…and Meloidogyne spp. ( Afolami and Fawole, 1991 , Kagoda et al, 2011 ). These nematodes however tend to have wide host ranges including legumes and various weed species, limiting the possibilities to use rotational legumes to control them ( Viaene et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…The analyses proposed by Jinks and Hayman (1953) and described in more detail by Hayman (1954aHayman ( , 1954b are robust in terms of genetic information generated and provide information on additive and dominance effects of genes, average degree of dominance, proportion of dominance, direction of dominance, distribution of genes, maternal and reciprocal effects, number of groups of genes that control a trait and exhibit dominance, ratio of dominant to recessive alleles in all the parents, and broad-sense (H 2 ) and narrow-sense (h 2 ) heritability. Hayman's (1954aHayman's ( , 1954b diallel analysis method has been used to study the mode of inheritance of various traits in several crops including barley (Hordeum vulgare L.) (Johnson, 1963;Hayter, 1972, 1973;Jana, 1975;Olsen, 1979;Douglas and Gordon, 1985;Caligari et al, 1987;Komatsuda et al, 1989), Brassicas (Ono and Takahata, 2000;Zhang and Takahata, 2001;Sparrow et al, 2004aSparrow et al, , 2004bTanaka and Niikura, 2006;Horisaki and Niikura, 2007), cotton (Gossypium hirsutum L.) (Verhalen et al, 1971;Innes et al, 1974;Luckett, 1989;Zhang et al, 2007), maize (Zea mays L.) Major, 1981a, 1981b;Hohls et al, 1996;Betrán et al, 2003;Srdić et al, 2007;Kagoda et al, 2011), pea (Pisum sativum L.) (Bencheikh and Gallais, 1996), peanut (Arachis hypogaea L.) (Gibori et al, 1978), radish (Raphanus sativus L.) (Iwata et al, 2000(Iwata et al, , 2004, rice (Oryza sativa L.) (Mohanty and Khush, 1985;Xu and Shen, 1991;…”
Section: Sashaydiall: a Sas Program For Hayman's Diallel Analysismentioning
confidence: 99%
“…Hayman's (1954a, 1954b) diallel analysis method has been used to study the mode of inheritance of various traits in several crops including barley ( Hordeum vulgare L.) (Johnson, 1963; Riggs and Hayter, 1972, 1973; Jana, 1975; Olsen, 1979; Douglas and Gordon, 1985; Caligari et al, 1987; Komatsuda et al, 1989), Brassicas (Ono and Takahata, 2000; Zhang and Takahata, 2001; Sparrow et al, 2004a, 2004b; Tanaka and Niikura, 2006; Horisaki and Niikura, 2007), cotton ( Gossypium hirsutum L.) (Verhalen et al, 1971; Innes et al, 1974; Luckett, 1989; Zhang et al, 2007), maize ( Zea mays L.) (Rood and Major, 1981a, 1981b; Hohls et al, 1996; Betrán et al, 2003; Srdić et al, 2007; Kagoda et al, 2011), pea ( Pisum sativum L.) (Bencheikh and Gallais, 1996), peanut ( Arachis hypogaea L.) (Gibori et al, 1978), radish ( Raphanus sativus L.) (Iwata et al, 2000, 2004), rice ( Oryza sativa L.) (Mohanty and Khush, 1985; Xu and Shen, 1991; Pooni et al, 1993; Chaubey et al, 1994; Kuo et al, 1997; Taguchi‐Shiobara et al, 1997; Nemoto et al, 2004), soybean [ Glycine max (L.) Merr.] (Spehar, 1995; Spehar and Galwey, 1996; Tukamuhabwa et al, 2002), sugarbeet ( Beta vulgaris L.) (Jolliffe and Arthur, 1993), tobacco ( Nicotiana rustica L.) (Jinks, 1954; Pooni et al, 1997), triticale (× Triticosecale Wittmack) (Mather and Poysa, 1983; Carrillo et al, 1985), and wheat ( Triticum aestivum L.) (Crumpacker and Allard, 1962; Klaimi and Qualset, 1973; Law et al, 1978; Danon and Eyal, 1990; Ghannadha et al, 1995; Wagoire et al, 1998), among others.…”
mentioning
confidence: 99%